If I ran the horse show - Worth, Bonnie; Mathieu, Joe; Ruiz, Aristides (London A Random House Group Cpmpany, 2013)
Calling all young equestrians and Cat (in the Hat) fanciers! In this latest installment of the Cat in the Hat's learning library, the Cat introduces Sally and Nick -- and beginning readers -- to all things horsey. At his Super-Tremendous-Stupendous Horse Show, the Cat explains how horses and people have worked together since ancient times; the difference between fillies, foals, yearlings, mares, colts, dams, sires, and stallions; horse anatomy from nose to tail; the work of a farrier, Western vs English riding; and much, much more -- including fun facts about 13 of the most popular horse breeds!
"I'm Ready for reading"
English stories
2
Keywords: English stories